PRAKTIK ILMU KETEKNIKAN GEOLOGI PERTAMBANGAN YANG BERKAITAN DENGAN PELEDAKAN BATUAN - Jarwanto, Jarwanto (Nusantara Hasana Journal, 2025)
This community service activity aimed to improve vocational high school (SMK) students’ understanding of the application of mining geological engineering, particularly in the aspect of rock blasting. Blasting is one of the main methods in mining operations used to fragment hard rock so that it can be easily excavated and transported. However, this material is still rarely understood technically by vocational secondary-level students. The activity was conducted in the form of theoretical outreach, simulation practice, and demonstrations of basic blasting design calculations. The materials delivered included basic blasting principles, types of explosives, blast hole geometry, safety factors, and environmental impacts. The results of the activity showed an increase in students’ conceptual understanding of rock blasting mechanisms, occupational safety, and the relationship between geological science and mining practices. This program contributes to strengthening the link and match between vocational education and the needs of the mining industry.